Reuse of public, genome‐wide, murine eosinophil expression data for hypotheses development. Issue 1 (14th May 2018) - Grace, Jillian O.; Malik, Astha; Reichman, Hadar; Munitz, Ariel; Barski, Artem; Fulkerson, Patricia C.
Abstract: The eosinophil (Eos) surface phenotype and activation state is altered after recruitment into tissues and after exposure to pro‐inflammatory cytokines. In addition, distinct Eos functional subsets have been described, suggesting that tissue‐specific responses for Eos contribute to organ homeostasis. Understanding the mechanisms by which Eos subsets achieve their tissue‐specific identity is currently an unmet goal for the eosinophil research community. Publicly archived expression data can be used to answer original questions, test and generate new hypotheses, and serve as a launching point for experimental design. With these goals in mind, we investigated the effect of genetic background, culture methods, and tissue residency on murine Eos gene expression using publicly available, genome‐wide expression data. Eos differentiated from cultures have a gene expression profile that is distinct from that of native homeostatic Eos; thus, researchers can repurpose published expression data to aid in selecting the appropriate culture method to study their gene of interest. In addition, we identified Eos lung‐ and gastrointestinal‐specific transcriptomes, highlighting the profound effect of local tissue environment on gene expression in a terminally differentiated granulocyte even at homeostasis. Expanding the "toolbox" of Eos researchers to include public‐data reuse can reduce redundancy, increase research efficiency, and lead to new biological insights. Abstract : Publicly archived eosinophil genome‐wide expression data can be used to answer original questions, generate new hypotheses, and serve as a launching point for experimental design.